2016
DOI: 10.1016/j.tins.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Plasticity in Human Motor Learning

Abstract: Summary There is accumulating evidence from behavioural, neurophysiological and neuroimaging studies that the acquisition of motor skills involves both perceptual and motor learning. Perceptual learning alters movements, motor learning and motor networks of the brain. Motor learning changes perceptual function and the brain’s sensory circuits. Here we review studies of both human limb movement and speech which indicate that plasticity in sensory and motor systems is reciprocally linked. Taken together, this po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
140
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(153 citation statements)
references
References 79 publications
9
140
1
3
Order By: Relevance
“…This was achieved by incorporating, into the target following phase, one of three explicit pattern recognition tasks (word, face, and object recognition) in a videogame-like interface. The combination of perceptual leaning and oculomotor training may mutually facilitate and reinforce the training effect of each other (Achtman, Green, & Bavelier, 2008; Ostry & Gribble, 2016). Besides we believed that this integrative learning approach (including engagement of attention, reinforcement, multiple stimulus dimensions, and multisensory inputs: continuous background music, auditory feedback using synthetic voices or pure tones, and auditory cue for a target item) helps promote generalizability to other tasks as demonstrated in previous perceptual learning studies (Deveau, Lovcik et al, 2014; Deveau, Ozer, et al, 2014; Deveau & Seitz, 2014; Li, Polat, Makous, & Bavelier, 2009; Xiao et al, 2008; Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This was achieved by incorporating, into the target following phase, one of three explicit pattern recognition tasks (word, face, and object recognition) in a videogame-like interface. The combination of perceptual leaning and oculomotor training may mutually facilitate and reinforce the training effect of each other (Achtman, Green, & Bavelier, 2008; Ostry & Gribble, 2016). Besides we believed that this integrative learning approach (including engagement of attention, reinforcement, multiple stimulus dimensions, and multisensory inputs: continuous background music, auditory feedback using synthetic voices or pure tones, and auditory cue for a target item) helps promote generalizability to other tasks as demonstrated in previous perceptual learning studies (Deveau, Lovcik et al, 2014; Deveau, Ozer, et al, 2014; Deveau & Seitz, 2014; Li, Polat, Makous, & Bavelier, 2009; Xiao et al, 2008; Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is presumable that finer force discrimination ability signaled more accurate information about motor error during piano practice and thereby facilitated fine motor control via the feedback error learning21. It is also possible that repetitive and prolonged provision of accurate sensory feedback in itself enhanced the ability of precise force control owing to a reciprocal link of neuroplasticity in the somatosensory and motor systems12. These postulations are further compatible not only with our observation of no correlations between these somatosensory and motor functions in the non-musicians, who never underwent extensive multimodal musical training, but also with a recent theoretical model of gene-environment interaction26.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has revealed a shared mechanism between motor and perceptual learning111213. For example, in speech production, adaptation to altered auditory feedback and altered somatosensory feedback results in perceptual shifts1415.…”
mentioning
confidence: 99%
“…Auditory feedback provides critical information for the learning and maintenance of feedforward motor commands during speech production (Houde & Jordan, 1998;Jones & Munhall, 2005), and plasticity in the auditory system drives changes in speech motor learning (Jones & Keough, 2008;Ostry & Gribble, 2016). Auditory feedback provides critical information for the learning and maintenance of feedforward motor commands during speech production (Houde & Jordan, 1998;Jones & Munhall, 2005), and plasticity in the auditory system drives changes in speech motor learning (Jones & Keough, 2008;Ostry & Gribble, 2016).…”
Section: Cerebellar Mechanisms Of Speech Motor Controlmentioning
confidence: 99%